When is Effort Contagious in New Venture Management Teams? Understanding the Contingencies of Social Motivation Theory - Nicola Breugst; Holger Patzelt; Dean A. Shepherd (Journal of Management Studies, 2020)
Consistent with social motivation theory, prior research on managerial motivation suggests that effort is contagious across management team members. In this study, we draw on belongingness theory to develop a model on important boundary conditions to social motivation theory in the management team context. The model predicts that new venture managers react to their teammates' higher effort levels by investing higher effort levels themselves primarily when they are confronted with a threat – namely, low venture performance and high environmental hostility – but that effort is less contagious when managers face little threat. We test our model with a sample of 103 new venture managers nested in 51 management teams in a longitudinal setting capturing managerial effort over 26~weeks. While we do not find a direct relationship between teammates' effort and a new venture manager's subsequent effort, we find support for the crucial role of threat in triggering the contagion of managerial effort. We discuss the contributions of our study for research on management teams, performance feedback, and entrepreneurial effort in new ventures.
Keywords: 650; entrepreneurial effort; entrepreneurial team; environmental hostility; firm performance; new venture management team; social motivation